Improvement of sewage sludge anaerobic digestion through synergistic effect combined trace elements enhancer with enzyme pretreatment and microbial community response. (January 2022) - Jiang, Xinru; Lyu, Qingyang; Bi, Liefeng; Liu, Yang; Xie, Yandong; Ji, Gaosheng; Huan, Chenchen; Xu, Lishan; Yan, Zhiying
Abstract: In this study, a double E strategy (enzymes and enhancer) characterized by high efficiency for enhancing sewage sludge anaerobic digestion (AD) is proposed. This strategy combines addition of trace elements (TEs) enhancer and enzyme pretreatment, inducing a synergistic effect on AD, and it is more effective and economical compared with TEs addition or enzyme pretreatment in isolation. When adding 400 U/g cocktail enzymes and 1.24% trance elements enhancers, the cumulative methane production and the maximum daily methane increased yield by 45.29% and 84.7%, respectively. According to microbial community analysis, the double E strategy significantly motivate the growth of acetogens and protein fermenting bacterium. The relative abundance of Fermentimonas and Lutispora increased by 6.15% and 5.4%, respectively. Archaeal community analysis and changes in the mcrA gene abundance demonstrate enrichment of hydrogenotrophic methanogens, with the methanogens exhibiting high vitalities and stress resistance. The double E strategy could be a promising way to improve industrial sewage sludge AD efficiency. Graphical abstract: Image 1 Highlights: Soluble protein content increased by 47.7% under low enzymes pretreatment. Enzymes and enhancers induced a synergistic effect on anaerobic digestion. Protein fermenting bacterium were abundant under the synergistic strategy. Hydrogenotrophic methanogens exhibiting high vitalities and stress resistance.